2011
DOI: 10.1371/journal.pone.0014487
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Rules for Coherent Group Motion in a Gregarious Vertebrate

Abstract: Individuals of gregarious species that initiate collective movement require mechanisms of cohesion in order to maintain advantages of group living. One fundamental question in the study of collective movement is what individual rules are employed when making movement decisions. Previous studies have revealed that group movements often depend on social interactions among individual members and specifically that collective decisions to move often follow a quorum-like response. However, these studies either did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…We describe these changes by a set of transition rates between the different behavioral states. Previous experiments conducted on small groups (41,42) have shown that the probability p 0→1 for a stationary individual to start walking is considerably enhanced by the presence of moving neighbors. Here, for the sake of simplicity, we ignore the weaker suppression effect of stationary neighbors and we also assume that p 1→0 , the inverse transition, possesses the same structure, as suggested in ref.…”
Section: Ecology Physicsmentioning
confidence: 99%
“…We describe these changes by a set of transition rates between the different behavioral states. Previous experiments conducted on small groups (41,42) have shown that the probability p 0→1 for a stationary individual to start walking is considerably enhanced by the presence of moving neighbors. Here, for the sake of simplicity, we ignore the weaker suppression effect of stationary neighbors and we also assume that p 1→0 , the inverse transition, possesses the same structure, as suggested in ref.…”
Section: Ecology Physicsmentioning
confidence: 99%
“…Substantial differences in knowledge or experience are likely to exist in such groups, and as individuals experience fewer repeated interactions, they are likely to be less certain about the knowledge or behavioral traits of others (Biro et al 2006). In the empirical studies with these conditions, research has instead focused on the mechanism(s) underlying information transfer, with the behavior of potential leaders either not measured and assumed to be constant (Pillot et al 2011;Stienessen and Parrish 2013) or kept constant through the use of model conspecifics (Ward et al 2008, although see Halloy et al 2007 for an example where robot conspecifics can exert different degrees of influence depending on their behavioral parameters). Other studies, by contrast, have related variation in individuals' tendency to influence group decisions to behavioral or morphological traits (i.e., who tries to lead, rather than how; Reebs 2001;Harcourt et al 2009;Schuett and Dall 2009;Freeman et al 2011;Burns et al 2012;Flack et al 2012;Brown and Irving 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Its generality was later verified in observations of sheep [11]. Despite being a collective movement model, actual movement through an environment is not a part of the model.…”
Section: Methodsmentioning
confidence: 99%